UPAYA HUKUM DALAM PERLINDUNGAN TANAH KAS DESA - Umi Supraptiningsih (Yuridika, 2010)
The protection toward the land, use for the village employees in place of salary, is really urgent to do. it is in order to avoid the distinction and the transferal of the land into irresponsible people. the land registration is one of the law protection forms in order to give law assurance as a preventive protection. in case, there are some actions causing the distinction and the transferal of the land, then there should be a firm lawenforcement and an explicit sanction.